Teshima Art Museum: Espacio arquitectónico, experiencia perceptiva y manipulación de la escala (ARQUISUR Revista, 2017)
Architectural space, perceptual experience and scale manipulation The present reflection paper develops, with a look strongly based on the direct experience of the space, and the goal to generate a balanced textual and visual discourse, a deepening in the design process involved in a singular work: the Museum of Art of Teshima. The museum is an initiatory work, without previous references, that finds its identity in the balance between architecture and art, and between art and nature, and unfolds itself in a conceptual space in which formal, expressive, functional and technical performances a re closely intertwined. The reflection is developed considering two main aspects: the perceptual experience and the manipulation of the scale, using a sieve of design attributes that includes among others: object quality, pregnance, abstraction, figuration and analogy, perceptive and haptic experience, fluency, scale of observation, and time perception.The work is a further developing of a previous research centered on the study of scale, as a fundamental attribute of the design process.
Keywords: architecture; art; scales; perception; creative process